Impact of age and socioeconomic status on treatment and survival from aggressive lymphoma: a UK population-based study of diffuse large B-cell lymphoma. Issue 6 (December 2015) - Smith, Alexandra; Crouch, Simon; Howell, Debra; Burton, Cathy; Patmore, Russell; Roman, Eve
Highlights: Age and performance status were predicative of treatment and survival. Sixty percent of patients ≥75 yrs were treated with curative intent. Performance status was more discriminatory of treatment and survival than age. Socio-economic factors were not predictive of survival. Clinical characteristics aide interpretation of socio-demographic treatment/outcome trends. Abstract: Aim: To examine the influence of patient's age and socio-economic status on treatment and outcome in diffuse large B-cell lymphoma (DLBCL); an aggressive curable cancer, with an incidence rate that increases markedly with age but varies little with socio-economic status. Methods: Set within a representative UK population of around 4 million, data are from an established patient cohort. This report includes all patients (≥18years) newly diagnosed with DLBCL 2004–2012, with follow-up to February 2015. Results: Of the 2137 patients (median age 70.2 years) diagnosed with denovo DLBCL, 1709 (80%) were treated curatively/intensively and 1161(54.3%) died during follow-up. Five-year overall and relative survival (RS) estimates were 46.2% (95% CI 44.0–48.4%) and 54.6% (52.1%-57.0%) respectively for all patients, and 58.5% (56.1–60.9%) and 67.0% (64.3–69.6%) for intensively treated patients. 96.3% of patients <55 years (366/380) and 96.4% of those with the best performance status (543/563) were treated curatively: 5-year RSs being 77.9% (73.1–82%) and 87.1% (82.5–90.6%) respectively. At the other end of the age/fitness spectrum, 33.3% of those ≥85 years (66/198) and 41.1% with the worst performance (94/225) were treated curatively: the corresponding 5-year RSs being 50.5% (27.1–69.0%) and 22.9% (14.0–33.2%). The proportion of patients whose cancer was fully staged fell with increasing age and worsening performance status. No socio-economic variations with treatment, stage at presentation or outcome were detected. Conclusions: Performance status is more discriminatory of survival than chronological age, with fitter patients benefiting from treatment across all ages. Socio-economic factors are not predictive of outcome in patients with DLBCL in the UK.